Financial Literacy Program for Housewives in Rubber Plantation Villages in Indonesia - Furbani, Widiastuti; Rini, Puspa; Bachtiar, Alfan; Nilfatri, Nilfatri; Pitri, Alisyah (Unram Journal of Community Service, 2024)
The Financial Literacy Program for Housewives in Rubber Plantation Village aims to improve understanding and skills in family financial management, especially among housewives vulnerable to income fluctuations. This activity was conducted online through the Zoom application and attended by 50 housewives. The methods include three-month interactive training, group discussions, and post-training mentoring. The results of the initial Survey showed that most participants did not have a monthly budget plan (80%), did not save regularly (70%), and did not understand the importance of debt management and insurance (85%). After the training, there was a significant increase in understanding and practice of financial management. As many as 65% of participants started preparing a monthly budget, 55% saved regularly, and 45% understood how to manage debt wisely. Although there are challenges in implementing financial literacy, especially related to income instability, this program has proven effective in increasing awareness and financial management skills. The final Survey also showed increased awareness of the importance of emergency funds and long-term financial plans, although the percentage is still relatively low. With this program, it is hoped that housewives in rubber plantation villages can be more independent and resilient and manage family finances better amid economic uncertainty